An analysis to detect exuberance and implosion in regional house prices in Turkey - Evren Ceritoglu; Seyit Mumin Cilasun; Ufuk Demiroglu; Aytul Ganioglu (Central Bank Review (CBR), 2019)
The aim of this paper is to find out whether there is exuberance in regional house prices in Turkey. For this purpose, we analyze real hedonic house prices and price to rent ratios countrywide as well as for 26 geographic regions at the NUTS2 level from January 2010 to January 2019. We perform the right-tailed unit root testing procedures developed by Phillips et al. (2015) and Phillips and Shi (2018) and use their real time date-stamping strategy to determine periods of explosiveness and implosion. Our empirical findings indicate that there were exuberance episodes in house prices in Turkey for multiple periods, where an important contributor to these dynamics was the largest housing market, İstanbul. We also detect exuberance in some other regions, particularly in the neighboring NUTS2 regions of İstanbul and in İzmir after around 2014. However, we find out that explosive price behavior turned into implosion in many regions starting from 2018.
Keywords: C22; G12; R21; 330; Hedonic house prices; Price-to-rent ratio; Explosive price behavior; Right-tailed unit root tests